KMU und Arbeitsplatzdynamik: Eine Analyse auf Basis der Beschäftigten-Historik - Thomas K. Bauer; Alexandra Schmucker; Matthias Vorell (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2008)
– This article uses the total population of firms, as contained in the Employee History ('Beschäftigten-Historik') of the IAB, to analyse the dynamics of employment in establishments of different size classes. This analysis is therefore the first of its kind to include all economic sectors for Germany. The results show that in 2005 approximately 69.6% of all employees subject to social security were working in small and medium-sized establishments with up to 250 employees. Furthermore, it becomes apparent that small and medium-sized firms contribute mostly to the reallocation of jobs and play an important role in the efficient allocation of labour. Our findings cast doubt on the traditional hypothesis that small and medium-sized firms are the main contributors to employment gains in the German economy. During the 2002-2005 period, characterized by a weak domestic economy, the number of employees liable to social security in large-scale enterprises decreased by 1.19%. All other segments of the firm population exhibited relatively larger losses.
Keywords: 330; Klein- und Mittelbetrieb; job turnover; IAB-Beschäftigtenhistorik; Beschäftigungsentwicklung; sozialversicherungspflichtige Arbeitnehmer; zusätzliche Arbeitsplätze; Arbeitsplatzabbau; Unternehmensgründung; Beschäftigungseffekte; regionaler Vergleich; Beschäftigungsschwankung; Beschäftigtenzahl; Betriebsgröße; Betriebsstilllegung; Ostdeutschland; Westdeutschland; Bundesrepublik Deutschland